The acoustic field on the axis of a circular cone - TYGIELSKI, Henryk; RDZANEK, Witold (Archives of Acoustics, 1984)
It was assumed in this paper that the sound source was placed on the surface of an ideal rigid circular cone. The vibration velocity amplitude at the source was constant. Solution of the wave equation in a system of spherical coordinates, by using the Kontorovich–Lebedev transformation, gave the acoustic potential. Expressions for the acoustic pressure on the axis of a circular cone were derived, and these calculations were represented graphically.